2017
DOI: 10.1111/jiec.12641
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Economic Implications of Distributed Additive Manufacturing: The Case of Injection Mold Tooling

Abstract: SummaryAdditive manufacturing (AM) holds great potentials in enabling superior engineering functionality, streamlining supply chains, and reducing life cycle impacts compared to conventional manufacturing (CM). This study estimates the net changes in supply-chain lead time, life cycle primary energy consumption, greenhouse gas (GHG) emissions, and life cycle costs (LCC) associated with AM technologies for the case of injection molding, to shed light on the environmental and economic advantages of a shift from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 29 publications
0
43
0
4
Order By: Relevance
“…Cerdas and colleagues () investigate the possibility for companies to accelerate product development and to consider new supply‐chain models by comparing a conventional mass scale centralized manufacturing system against a 3D printing‐enabled distributed manufacturing system. Huang and colleagues () provide an interprocess comparison of injection molding pathways with conventionally and additively manufactured tooling, combining an assessment of supply‐chain lead time, life cycle energy consumption, emissions, and life cycle costs. This perspective is complemented in a column by Quinlan and colleagues () who, after surveying the material deposition speeds achieved by available AM systems, evaluate industrial, retailer, and consumer perspectives in AM, thereby offering insight as to how AM will challenge traditional models of durable goods provision.…”
Section: The Special Issue: Charting Impacts Across the Product Life mentioning
confidence: 99%
“…Cerdas and colleagues () investigate the possibility for companies to accelerate product development and to consider new supply‐chain models by comparing a conventional mass scale centralized manufacturing system against a 3D printing‐enabled distributed manufacturing system. Huang and colleagues () provide an interprocess comparison of injection molding pathways with conventionally and additively manufactured tooling, combining an assessment of supply‐chain lead time, life cycle energy consumption, emissions, and life cycle costs. This perspective is complemented in a column by Quinlan and colleagues () who, after surveying the material deposition speeds achieved by available AM systems, evaluate industrial, retailer, and consumer perspectives in AM, thereby offering insight as to how AM will challenge traditional models of durable goods provision.…”
Section: The Special Issue: Charting Impacts Across the Product Life mentioning
confidence: 99%
“…By following the part's geometry, the part is cooled in a much more uniform manner. The fabrication of tooling for injection molding using the L-PBF process decreases geometric constraints, while decreasing build times and cost [14][15][16]. In the past, various independent research studies have been reported on tooling with conformal cooling channels [4,15,16,26,27,37].…”
Section: As-printed L-pbf Mold Evaluationmentioning
confidence: 99%
“…This process repeats for all layers until the part is created, as shown in Additive manufacturing is a disruptive technology with annual sales expected to reach $12.1 billion with a growth of 35% during 2018 [13]. The fabrication of tooling for injection molding using L-PBF provides design freedom, while decreasing build times and cost [14][15][16]. Additionally, 3D printing manufacturers could fabricate tooling for injection molding with a variety of materials, such as stainless steels, tool steels, and aluminum alloys [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations